1D Van der Waals Polymers with Nonlinear Optical Performance Approaching Theoretical Upper Limit - Yang, Jingyu; Deng, Jun; Pan, Jinbo; Zhu, Yongqian; Zhang, Yan‐Fang; Li, Yuhui; Sun, Jia‐Tao; Du, Shixuan (Advanced functional materials, 2023)
Nonlinear optical (NLO) materials are of great importance for applications in lasers, atomic clocks, free‐space communication, etc. Herein, inspired by the recent prediction of excellent second harmonic generation (SHG) performance in van der Waals (vdW) materials with 1D building blocks, 14 new NLO materials are found from 244 bulk crystals constructed with 1D polymers using high‐throughput first‐principles calculations. Nearly half of the new NLO materials exhibit superior NLO performance with SHG susceptibilities approaching the theoretical upper limit. The 2D form of 11 candidates inherits the NLO property covering UV, visible, and infrared regions. Bader charge analysis reveals that the SHG susceptibility is determined by the charge difference of ions on the chains. Finally, it is proposed that superior NLO materials can be found in materials with proper bandgaps and large charge differences on the chains. This work not only screens out candidates with outstanding NLO performance in vdW materials with 1D building blocks but also provides a guideline for the search and design of NLO vdW 1D polymer patterns with excellent NLO properties. By screening bulk van der Waals (vdW) materials featuring 1D chains, materials with exceptional properties are identified, including large second harmonic generation (SHG) susceptibility, appropriate bandgap, and birefringence. These materials' nonlinear optical (NLO) properties are intricately linked to the stacking prototypes of their chains and the charge difference of ions on the chains.